+0  
 
0
234
1
avatar+314 

how you do this

ISmellGood  Oct 20, 2017
 #1
avatar+91116 
+1

We have that

 

(-3)^2 + m(-3) + n  = 0

 

9  - 3m + n  = 0      →     n =   3m - 9       (1)

 

If x = -3 is the only possible solution...we only have one root...so......the discriminant must  = 0

 

So

 

m^2  -  4n  = 0     sub (1)  into this

 

m^2 - 4 [ 3m - 9 ]  = 0   simplify

 

m^2 - 12m + 36  =  0       factor

 

(m - 6)^2  = 0

 

Which implies that  m  = 6

 

And n  = 3(6) - 9  = 9

 

So....our function is   x^2 + 6x + 9 = 0

Check to see that  x = -3  is the only root

 

 

cool cool cool

CPhill  Oct 20, 2017

11 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.